Monitoring the collection of the Ustimivsky Dendrological Park for detection of harmful agents - Bilyk, O.; Pysarenko, V.; Pospielova, G.; Kovalenko, N. (Scientific Progress & Innovations, 2025)
The Ustymivsky Dendrological Park is one of the oldest and most valuable nature conservation areas in Ukraine, established to preserve, study, and introduce tree and shrub species in the steppe zone. Its dendroflora collection comprises more than 470 taxa, ensuring unique biodiversity, yet requiring constant monitoring and protection. The preservation of plants ex situ is complicated by the influence of multiple stress factors, including climate change, abiotic stressors, as well as invasive and native pests. The mass spread of phytophagous insects in collection plantations may result in the loss of valuable species, a decline in ornamental value, and reduced ecological stability of the park ecosystem. Comprehensive long-term studies of the phytosanitary condition of the dendrological park made it possible to identify more than 50 pest species. The most dangerous among them are adelgids, the European pine sawfly (Neodiprion sertifer), spindle ermine moth (Yponomeuta cagnagellus), the ash blister beetle (Agrilus convexicollis), rose chafers (Cetoniinae), the fall webworm (Hyphantria cunea), and the horse chestnut leaf miner (Cameraria ohridella). The population dynamics of these phytophages, their developmental characteristics, seasonal patterns of harmfulness, and the scale of damage to individual tree and shrub species were determined. Special emphasis was placed on invasive species that actively expand their range under climate warming and represent a serious threat to introduced plants. The results of the research confirmed that the exclusive use of mechanical and biological control methods is insufficient to ensure the stability of plantations within the protected area. The most effective strategy has proven to be an integrated approach that combines regular monitoring, pest population forecasting, biological regulation techniques, and the limited application of chemical treatments while complying with ecological safety standards. The findings are of significant practical importance for improving the protection system of the dendrological park’s collections, conserving the plant gene pool, and maintaining biodiversity. They may serve as a scientific basis for the development of long-term phytosanitary monitoring and management programs for plantations in protected natural areas.